2017
DOI: 10.1158/1535-7163.mct-16-0519
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 Inhibition Synergistically Enhances the Effects of Magnetic Fluid Hyperthermia in Ovarian Cancer

Abstract: Hyperthermia has been investigated as a potential treatment for cancer. However, specificity in hyperthermia application remains a significant challenge. Magnetic fluid hyperthermia (MFH) may be an alternative to surpass such a challenge, but implications of MFH at the cellular level are not well understood. Therefore, the present work focused on the examination of gene expression after MFH treatment and using such information to identify target genes that when inhibited could produce an enhanced therapeutic o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…Cells were cultured on 75 cm 2 flasks (Eppendorf, Hamburg, Germany) with RPMI 1640 medium supplemented with 15% FBS, 2 g/L sodium bicarbonate, 0.1% gentamicin, and maintained at 37°C and 5% CO 2 as described elsewhere. 11 Cells were split every 3 days at a 1:3 split ratio with an 80-90% of confluence, keeping passage numbers below twenty.…”
Section: Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were cultured on 75 cm 2 flasks (Eppendorf, Hamburg, Germany) with RPMI 1640 medium supplemented with 15% FBS, 2 g/L sodium bicarbonate, 0.1% gentamicin, and maintained at 37°C and 5% CO 2 as described elsewhere. 11 Cells were split every 3 days at a 1:3 split ratio with an 80-90% of confluence, keeping passage numbers below twenty.…”
Section: Cell Culturesmentioning
confidence: 99%
“…In addition, significant tumor volume reductions were observed in vivo after PES/MFH co-administration in mice bearing intraperitoneal ovarian tumors. 11 Despite promising results, one of the limitations for the clinical translation of drug/MFH combination therapies is the required optimal concentrations of drugs and nanoparticles in tumor cells, which is difficult to attain in the clinical setting. In addition to poor penetration of drugs into tumors, efficient drug uptake by cancer cells is limited by the chemical composition of the drug molecule, especially for hydrophilic molecules with unpredictable active uptake pathways.…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that the effect of hyperthermia in orthotopic ovarian models with iron oxide nanoparticles irradiated by AMF on tumor suppression was enhanced when used in combination with knockdown of the heat shock protein (HSP) 70 gene by treatment with DOPC liposomal siRNA. 78) Collectively, we demonstrated that the efficacy of hyperthermia in cancer therapy could be improved by manipulating the biological response under heat stress.…”
Section: Improved Efficacy Of Hyperthermia By Inhibiting a Hyperthermmentioning
confidence: 94%
“…74) The feature by which magnetic nanocarriers generate heat under AMF allows magnet nanocarriers to be applied for magnetic hyperthermia as well. [75][76][77][78] Magnetic nanocarriers with unique magnetic properties are able to improve the signal-to-noise ratio in magnetic resonance imaging (MRI), and have been widely applied as MRI contrast agents, useful both in MRI-guided diagnostics and therapeutics. 79,80) US has been used extensively in clinics for diagnosis and therapy, due to its intrinsic tissue penetration and high safety.…”
Section: Activation In Response To External Stimulimentioning
confidence: 99%
“…The inhibition of HSP90 could sensitize LCSCs to magnetic hyperthermia and enhanced antitumor effects in vitro and in vivo. Court et al also found that HSPA6 encoding the heat shock protein 70 was upregulated in ovarian cancer cells after the cells were incubated with carboxymethyl dextran coated iron oxide nanoparticles and then exposed to an AMF (36 kA/m, 245 kHz) for 30 min to induce a temperature rise to 43 ∘ C [66]. They also demonstrated that HSP70 inhibition synergistically enhanced the effects of magnetic fluid hyperthermia in ovarian cancer.…”
Section: Mechanismsmentioning
confidence: 94%